Model Implementasi Corporate Social Responsibility Program Kemitraan pada Mitra Binaan Badan Usaha Milik Negara di Provinsi Kalimantan Selatan - Mentayani, Ida; Rusmanto, Rusmanto (Jurnal Aplikasi Manajemen, 2016)
This study aimed to identify the CSR implementation model, analyze and evaluate CSR implementation stages of the partnership program then formulate CSR implementation model partnership program of SOEs in South Kalimantan. The population of this studyis all the partners in the partnership program of SOEs in South Kalimantan. Sampling was done by purposive sampling method. Purposive sampling method applied because in this study required intensive interaction with subjects of this study, so the subjects of this study are selected based on the specific consideration (judgment). The specific consideration that became the criteria, so that SMEs in the samples of this study were the willingness of subjects (the partners) to become involved in this study and has been trained partners SOE for at least 2 years.Based on these criteria then obtained a total sample amounted 100 pieces SMEs trained partners. The data processed by individuals interview intensively, Focus Group Discussion and literature. The data analyzedby descriptive analysis method. The Implementation model of Corporate Social Responsibility (CSR) is a program partnership of SOEs in SouthÂ  Kalimantan province to SMEs as its established partners consists of the stages of planning, preparation stage, the stage of implementation, monitoring and evaluation stages.